Clothing-related burns in New South Wales, Australia: Impact of legislation on a continuing problem. Issue 1 (February 2015) - Harvey, Lara A.; Connolley, Siobhan; Harvey, John G.
Highlights Clothing related burns remain relatively rare in NSW (2% of all burn injury hospitalisations). Hospitalisations for all clothing burns have decreased by 4% per year over last 15 years. Hospitalisation for nightwear related burns has decreased at significantly faster rate (7.4% per year) than other clothing burns (2.5% per year). Accelerant use, cigarettes, loose clothing and angle grinders were common risk factors.